2022
DOI: 10.1186/s12877-022-03045-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and engagement of naturally occurring retirement communities to support healthy aging in Canada: A set of methods for replication

Abstract: Background Naturally occurring retirement communities (NORCs), unplanned communities with a high proportion of older adult residents, offer a model to support older adults to age well in place. The aim of this paper is to provide a comprehensive description of the methods used to identify and engage NORCs appropriate for the development of supportive service programming in Canada. Methods Three steps were used to identify and select NORCs in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…Maricruz Rivera-Hernandez et al found that despite a significant increase in the percentage of older homeowners and renters, the number of NORCs slightly declined over the ten-year period, confirming the existence of different patterns of NORC emergence, disappearance, and persistence [8]. Likewise, in Canada, Vincent G. DePaul developed and mapped out Dissemination Areas (DAs), choosing four cities to establish NORCs that include supportive service programs [13]. Conversely, this research employs census data to analyze the distribution of NORCs across Australia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Maricruz Rivera-Hernandez et al found that despite a significant increase in the percentage of older homeowners and renters, the number of NORCs slightly declined over the ten-year period, confirming the existence of different patterns of NORC emergence, disappearance, and persistence [8]. Likewise, in Canada, Vincent G. DePaul developed and mapped out Dissemination Areas (DAs), choosing four cities to establish NORCs that include supportive service programs [13]. Conversely, this research employs census data to analyze the distribution of NORCs across Australia.…”
Section: Discussionmentioning
confidence: 98%
“…Based on census data from 2000 to 2010, maps were created and analyzed using U.S. census tracts, with each tract representing approximately 4000 residents (ranging from 1200 to 8000) [8]. Due to differences in census unit sizes across countries, Vincent G. DePaul et al in Canada used Dissemination Areas (DAs) as the unit of analysis, with each area comprising 400 to 700 individuals [13]. The smaller clusters allow for more precise identification of NORCs.…”
Section: Introductionmentioning
confidence: 99%
“…The study suggested that NORC-SSPs have the potential to be an alternative model for supporting aging in place. DePaul, et al (2022) Created six NORC and supportive services programs in Ontario, Canada, to draw lessons and approaches that can be replicated in other communities.…”
Section: Abstract Co-occurrence Analysismentioning
confidence: 99%
“…Las necesidades de los mayores son muy amplias: afectivas, sanitarias, de acompañamiento o de entretenimiento entre otras (DePaul et al, 2022). Esto hace que las personas objeto de la comunicación de las ONG especializadas en personas mayores sea muy amplia (Plataforma del Voluntariado de España, 2020).…”
unclassified